Inclusive education and the plight of children without legal documentation: A case study of Cosmo Oasis in Johannesburg, South Africa - Matanhire, Vimbayi (University of the Witwatersrand, Johannesburg, 2024)
Children without documentation are excluded from formal school due to contestations and contradictions between the South African Constitution and the Admission Policy for Ordinary Schools and the practices of the Department of Home Affairs alongside legislative gaps and inconsistencies in South African schools regarding the admission of children without legal identification documents. This study investigated the plight of children without legal documents in relation to inclusive education in South Africa using a case study of a non- governmental organisation named Cosmo Oasis. I argue that a human rights approach to inclusive education within the social model paradigm is essential for this study because education is in itself a human right. I further develop a framework of inclusive education for undocumented children and outline the intricacies surrounding the origins and debates around the universality and enjoyment of human rights specifically by children without documentation. This study was a qualitative study that used mixed methods and it had the characteristics of a case study. Semi-structured audio-recorded interviews and questionnaires with open and closed questions were used as data collection tools. Data was analysed using qualitative data analysis methods by organising and sorting data into major themes and presented in the form of figures, tables, excerpts and descriptions. The findings of the study showed that, the South African education system was not inclusive to children without legal documents. These children are not integrated into the mainstream leading to varied socio-economic and political implications on the children without documents, their parents and on the South African education system. Contradictions between policies, the legal aspect, the Home Affairs Department, revealed the contestation between citizenship rights and problems with the social contract which continues to create an impasse between the realisation of rights by non-citizens and the rigidness of the social contract.
A research report submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Inclusive education; children without documentation; human rights; social contract; SDG-4: Quality education